The factor associated with moderate to high disease activity of Rheumatoid arthritis - Chitpet, Patamarwadee (Region 11 Medical Journal, 2024)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterised by joint inflammation and destruction. RA has been noted as a major cause of inflammatory disability and increased mortality. Early detection of the disease and initiation of disease-modifying drugs can reduce the progression of disease to severe state. Objective: This study aimed to characterize the clinical presentation of RA and to describe the factors associated with disease severity among patients with RA. Method: This was a cross-sectional study conducted among patients with confirmed RA attending the Rheumatic outpatient clinic, Surat Thani hospital, between September 2023 and January 2024. Demographic data and clinical factors associated with disease severity were collected. RA disease activity was assessed using the RA Disease Activity Score (DAS28)-ESR. Results: A total of 465 participants were enrolled, the majority of the participants were female. The median age of the population was 58 (IQR 50,65) years. Forty-four percent of the study population had moderate and high disease activity. Only 3.4 percent had high disease activity based on the DAS28-ESR. Female, Diabetes, early joint space narrowing and Glucocorticoid use were significantly associated with moderate to severe disease activity (OR 2.7, 95%CI 1.4-5.0, p=0.002; OR 2.7, 95%CI 1.2-5.9, p=0.015; OR 1.6 95%CI 1.1-2.6, p=0.029; OR 2.3 95%CI 1.5-3.6, p< 0.001, respectively). Conclusion: Female, Diabetes, early joint space narrowing and Glucocorticoid use were associated with disease severity, close monitoring and tight control strategy in these patients can achieve better clinical outcomes.